2012
DOI: 10.1159/000337717
|View full text |Cite
|
Sign up to set email alerts
|

Maternal C-Reactive Protein at Hospital Admission Is a Simple Predictor of Funisitis in Preterm Premature Rupture of Membranes

Abstract: Aim: To analyze the prognostic value of maternal serum C-reactive protein (CRP) in predicting funisitis in patients with preterm premature rupture of membranes (pPROM). Methods: 66 patients (gestational age 24–33 weeks) hospitalized 1–12 h after pPROM were enrolled. White blood cell count (WBC), platelet count (PLT) and plasma concentration of CRP were assessed every 3 days. Histological evidence of chorioamnionitis and funisitis was obtained post-partum. Receiver operating characteristic (ROC) curves were emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
4
17
1
1
Order By: Relevance
“…It is due to the fact that critical CRP values vary greatly from 5 to 40 mg/l (35). A study by Perrone et al did not prove any significant prognostic value of the WBC count, the same as our study (30). Based on these and other studies, Lee et al suggest that in practice it is worth using the CRP value as an indicator of early-onset neonatal sepsis and a prognostic test of funisitis rather than a diagnostic indicator.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It is due to the fact that critical CRP values vary greatly from 5 to 40 mg/l (35). A study by Perrone et al did not prove any significant prognostic value of the WBC count, the same as our study (30). Based on these and other studies, Lee et al suggest that in practice it is worth using the CRP value as an indicator of early-onset neonatal sepsis and a prognostic test of funisitis rather than a diagnostic indicator.…”
Section: Discussionsupporting
confidence: 69%
“…The importance of CRP levels in serum for the diagnosis of funisitis / chorioamnionitis (27)(28)(29)(30), for the determination of neonatal sepsis (31) and the association between neonatal infection and funisitis / chorioamnionitis are discussed in many works of various authors (32)(33). For example, van de Laar made a very important review of scientific works.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated maternal plasma concentrations of inflammatory cytokines in preterm gestations complicated by PTL or pPROM are associated with an increased risk of intra-amniotic infection [22, 24, 34, 41, 62, 63, 68, 125, 126, 141, 143, 198]. The findings herein demonstrate that MIAC is associated with decreased maternal plasma concentrations of soluble α-klotho.…”
Section: Commentsmentioning
confidence: 57%
“…The presence of MIAC is associated with increased risk of adverse perinatal outcomes, such as early preterm birth[164, 165, 171, 177, 202, 207], neonatal sepsis[104, 167], bronchopulmonary dysplasia[48, 206], neonatal white matter brain lesions[203, 210], and cerebral palsy[13, 14, 176, 205, 209]. Although MIAC is considered to be confined to the amniotic cavity and not a systemic condition, studies with flow cytometry have shown phenotypic and metabolic changes in leukocytes[45, 46] as well as changes in maternal cytokines concentration [22, 24, 34, 41, 62, 63, 68, 125, 126, 141, 143, 198]. These observations suggest that biomarkers for MIAC may be found in the maternal circulation.…”
Section: Introductionmentioning
confidence: 99%
“…This breakdown of the DGC could have deleterious effects on plasma membrane stability. In a normal pregnancy, the balance between MMP activation and inhibition is responsible for both minor adjustments necessary to accommodate an enlarging fetus, as well as major changes involved in the initiation of labor and rupture of membranes (ROM) [6,8,9,10]. Increased MMP activity causes degradation of the ECM and separation of the fetal membranes (FM), significantly changing the tensile strength and predisposing to preterm labor or FM rupture.…”
Section: Introductionmentioning
confidence: 99%